Racialized and Gendered Constructions of the “Ideal Server”: Contesting Historical Occupational Discourses of Restaurant Service - Dempsey, Sarah E. (Frontiers in Sustainable Food Systems, 2021)
This essay takes a discourse-centered approach to understanding the historically contingent construction of restaurant service as a devalued occupational identity, showing how service is actively constructed as low wage and organized along hierarchies of gender, race, and class. These discursive constructions shape the relative visibility and legibility of workers as fully deserving of rights, compensation, and dignity. Building on prior research on the struggle over meanings of work, occupational identity, and gendered and racialized job segregation, the essay begins by tracing constructions of the “ideal server” predating the contemporary rise of restaurants from relations of servitude within and beyond the plantation economy, to the eventual entrenchment of tipping, and the gendered and feminized constructions of domestic service. It discusses racialized and gendered relations of servitude in the Pullman Company's dining cars and the eventual white feminization of waitressing. Adopting a historical narrative built on secondary literatures, it demonstrates the centrality of race, gender, and class to early occupational formations of service. It highlights how employers have cultivated occupational hierarchies and divisions as well as efforts by restaurant workers to transform how their labor is valued and compensated.